Assessment of Health Care Workers Compliance to the Guidelines of Disinfection and Sterilization - Alris, Feras Fahad A; Almaeen, Mohammed Hammad O; Alarjan, Abdullah Wufuq M; Alzarea, Abdullah Ahmed; A Albadi, Tariq Abdulhadi; Alruwaili, Mohammed Mons N; Alrayes, Musab F.; Al Etesh, Nashmi Saloum (International Journal of Innovative Research in Medical Science, 2017)
Health care workers’ compliance with infection control practices and principles is vital in preventing the spread of disease. Lack of compliance and conform with scientifically recognized guidelines has in regards to infection control led to many outbreaks of infectious diseases. Over visits to primary health cares and collecting responses in regarding of the standards, 67% of them were done in positive manner. Around 90% of responses regarding cleaning the area, dealing with the garbage were appropriate, while less than 15% of the responses indicated that the health care workers (particularly the physicians) were using hand gloves After providing some recommendations to the health care workers, hand hygiene and wearing gloves had been improved, which will have a positive impact on controlling of infections.